Testing soccer players - Svensson, M.; Drust, B. (Journal of Sports Sciences, 2005)
To cope with the physiological demands of soccer, players must be competent across several fitness components. The use of fitness tests in the laboratory and field assist in examining soccer players' capabilities for performance both at the amateur and elite levels. Laboratory tests provide a useful indication of players' general fitness. Accurate test results can be obtained with the use of a thorough methodology and reliable equipment. Laboratory tests are used sparingly during the season because of the time-consuming nature of the tests. Instead, tests are generally carried out at the start and end of the pre-season period to evaluate the effectiveness of specific training interventions. Field tests provide results that are specific to the sport and are therefore more valid than laboratory tests. The reduced cost, use of minimal equipment and the ease with which tests can be conducted make them more convenient for extensive use throughout the season. Although data from laboratory and field tests provide a good indication of general and soccer-specific fitness, individual test results cannot be used to predict performance in match-play conclusively because of the complex nature of performance in competition. Fitness tests in conjunction with physiological data should be used for monitoring changes in players' fitness and for guiding their training prescription.